Proceso de adquisición de bienes y servicios de la “Gobernación de la Provincia de Los Ríos - Narváez Ramos, Thully Corelly (2018)
The Governorate of the Province of Los Ríos is an institution of character public, whose purpose is to provide services to citizens, where the acquisition of their resources are regulated by the Ministry of Finance; the state institutions that acquire Products, Goods and Services under the modality of PUBLIC PROCUREMENT OR ALSO CALLED PUBLIC PURCHASES. To carry out the hiring, there is a legal framework proposed by the Ecuadorian government, whose objectives are to guide, regulate and supervise the processes of public competitions. A good acquisition process allows us to achieve the goals institutions in an agile and responsible manner, where it is essential that they be planned in a appropriate all purchases that will be made throughout the year. In every government institution you must participate through competitions public, which makes it possible to make internal processes transparent and whose purpose is to comply with the planning of public institutions; This is where the interest to develop this case study called, Process of acquisition of goods and services of the "Gobernación" of the Province of Los Ríos. " The staff of the Interior was interviewed with the objective of knowing the way in which they carry out the acquisition processes, and if they are carried out according to the regulations current legal also to know the computer systems they use and problems that they can be presented internally and externally. In relation to the limitations that were presented we can indicate that the most notable are the confidentiality of institutional information and the lack of time of who helped with the data obtained. This case study will focus on the procurement processes of the Government of the Province of Los Ríos, from the stage of planning until the termination of the contract is given. This degree work was developed according to the subline of the accounting and auditing career "Information management accountant".